A New Trend in Recording Subgingival Tissue around an Implant While Making a Direct Abutment Impression - Suryakant C. Deogade; Sneha S. Mantri; Gunjan Dube; Radhika Shrivastava; Syed Noorani (Case Reports in Dentistry)
A successful implant-supported restoration must provide adequate function and esthetics. Osseointegrated implants have given an alternative choice for patients who have lost their teeth. Most commonly encountered problems while doing a transfer from patient to the master cast in restoring implant-supported crowns are an uneven distribution of occlusal loads and undue torquing forces on the various elements of implant. This is caused due to poor fit of frameworks connected to implant, which further leads to marginal bone loss, loosening of screws, fatigue fracture of implant components, and ultimately implant failure. This paper presents a simplified and easy solution to overcome such problems by introducing an innovative gingival retraction system for restoring implant-supported crowns to achieve superior and predictable long-term outcomes.